2018
DOI: 10.14687/jhs.v15i2.5343
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the attitudes of midwives and nurses towards gender roles and the influencing factors<p>Ebe ve hemşirelerin toplumsal cinsiyet rollerine ilişkin tutumları ve etkileyen faktörlerin incelenmesi

Abstract: AimThe study was conducted to determine the attitudes of midwives and nurses working in a university hospital in the Black Sea Region towards gender roles and influencing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
3
8
0
6
Order By: Relevance
“…Similar studies in literature also reported that students in health departments had more egalitarian attitudes towards gender roles. 20,21,26,27 An important finding of the present study was that the university students enroled in the health Abbreviations: F, one-way analysis of variance; SD, standard deviation; t, independent samples t test. *p < 0.05.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similar studies in literature also reported that students in health departments had more egalitarian attitudes towards gender roles. 20,21,26,27 An important finding of the present study was that the university students enroled in the health Abbreviations: F, one-way analysis of variance; SD, standard deviation; t, independent samples t test. *p < 0.05.…”
Section: Discussionmentioning
confidence: 75%
“…Of all the students who accepted to participate in the study, 73.1% were female and 33.2% were fourth-year students; average age was 20.70 ± 1.93 (min-max, [17][18][19][20][21][22][23][24][25][26][27][28][29]; and average number of siblings was 4.52 ± 2.13. In addition, 55.1% of the mothers graduated from primary school, and 41.2% of the fathers graduated from secondary school.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies, it was found that students studying in health-related departments of universities exhibited egalitarian attitudes towards gender roles, however, their attitudes were affected by various factors (gender, age, educational level, educational level of the mother and father, employment or unemployment, marital status, duration of marriage, etc.) and that they also had negative attitudes (Zeyneloğlu & Terzioğlu, 2011;Direk & Irmak, 2017;Aktaş et. al.…”
Section: Introductionmentioning
confidence: 99%
“…15 Aktaş ve arkadaşlarının (2018) hemşire ve ebelerin toplumsal cinsiyet rollerine yönelik tutumlarını ve etkileyen faktörleri ele aldıkları bir çalışmada; cinsiyet, yaş, medeni durum ve annelerin eğitim düzeyinin toplumsal cinsiyet rolleri üzerinde etkili olduğu belirlenmiştir. 11 Zeybek ve Kurşun (2019) tıp fakültesindeki öğrencilerinin toplumsal cinsiyet rollerine yönelik tutumlarını değerlendirdikleri çalışmada; cinsiyet, doğum yeri, aile tipi, kardeş sayısı, ailenin ekonomik durumu, annenin ve babanın eğitim durumu, annenin çalışma durumu ve uzun süre yaşanılan bölgenin toplumsal cinsiyet rolleri üzerinde etkili olduğunu ifade etmişlerdir. 19…”
Section: Introductionunclassified